Can participatory video-based extension increase awareness and knowledge of climate adaptation practices? Insights from rural Kenya - Ndegwa, Michael K.; Ringler, Claudia; Muteti, Francisca N.; Kato, Edward; Bryan, Elizabeth (International Food Policy Research Institute, 2023)
Climate-smart agriculture (CSA) has been promoted as a framework to identify a set of solutions that simultaneously sustain agricultural productivity and incomes, increase the resilience of agriculture, and reduce greenhouse gas emissions. However, it has proven to be challenging to reach women farmers with information on CSA practices. This note summarizes results from a study that assessed whether participatory video-based extension approaches tailored to women’s preferred CSA approaches could reduce the gender gap in awareness and adoption of CSA practices in Kenya. The findings suggest that watching the videos increased awareness of the CSA practices promoted in the videos as well as other practices. However, watching the videos did not increase the adoption of the CSA practices. We propose strategies to strengthen the uptake of CSA practices alongside participatory video-based extension.